An Analysis of Academic Entitlement Among Undergraduate Student - Siti Dini Fakhriya (Ma'soem University, 2025)
Academic entitlement is a belief that has become one of the issues in higher education. The purpose of this study is to determine the academic entitlement of undergraduate students according to their gender and involvement in organizations. The study involved 159 undergraduate students from the Faculty of Psychology at UIN Raden Fatah Palembang, who answered the online survey. The quantitative method will be applied. The instrument used academic entitlement scale by Chowning and Campbell's (2009) consist of 15 items from two factors, 10 items that evaluate externalized responsibilities, and 5 items that evaluate entitled expectations. The difference in academic entitlement by gender and organization participation is examined using a descriptive statistic and t-test. The results reveal that while there is a significant difference in academic entitlement (AE) based on organization participation, there is no significant difference in AE based on gender. Academic entitlement could occur in the university and it could lead to misconduct behavior, therefore future research should explore about the factor and impact from academic entitlement to address the potential development of academic entitlement in undergraduate student